The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10006-015-0493-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intraoperative time measurements between osseous reconstructions with free fibula flaps applying computer-aided designed/computer-aided manufactured and conventional techniques

Abstract: Despite the advantages of the CAD/CAM technique, including reduced ischemia time of osteocutaneous fibula flaps, there is no impact on total reconstruction time or flap survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…This approach was also followed by Rustemeyer et al in their investigation of intraoperative times in osseous reconstructions with free fibular grafts. No significant differences were found between the CAD/ CAM group and the conventional implant group (42). This was also shown by Ritschl et al (43) who also revealed no significant differences between these groups (43).…”
Section: Discussionsupporting
confidence: 72%
“…This approach was also followed by Rustemeyer et al in their investigation of intraoperative times in osseous reconstructions with free fibular grafts. No significant differences were found between the CAD/ CAM group and the conventional implant group (42). This was also shown by Ritschl et al (43) who also revealed no significant differences between these groups (43).…”
Section: Discussionsupporting
confidence: 72%
“…Using CAD/CAM guides and prebent plates can help to shorten the operation and flap ischemic times. 57 However, the total operation and flap ischemic times did not differ from the averages for the same operation. We believe this was because of the extra time needed to shave the fibula and to rebend the plates to deal with the intraoperative change.…”
Section: Discussionmentioning
confidence: 88%
“…17 However, there are no standard procedures for dealing with an intraoperative change in defect size, and CAD/CAM guides may not always be applicable as planned.…”
Section: Introductionmentioning
confidence: 99%
“…As far this workflow solution was just used for fibula graft but could also be applied to other bone grafts like scapula or iliac crest flaps [ 6 , 22 ]. In literature assessment of surgical time regarding CAD/CAM procedures is heterogenic but mostly states time reduction [ 7 , 10 , 23 ]. The percepted reduction of surgical time has not been tested here, but leads to a lower risk of general complications [ 11 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus the effect of reduction of surgery time is a result of a transition of manpower into the pre-surgical phase outside of the OR. The saved surgery time is thus only redeployed as already mentioned [ 7 , 23 ]. Overall there is still an economization as only one person is needed for planning instead of a whole OR team.…”
Section: Discussionmentioning
confidence: 99%